Citra Perempuan Jawa Dalam Teks Suluk Tenun - Fatmawati, Andriyana; Insani, Nur Hanifah (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2020)
Suluk Tenun reflects the image of Javanese women based on the background of Islamic religious traditions. Judging from the cultural feminism approach, this research uses descriptive qualitative methods and modern philology, which aims to describe the image of Javanese women listed in the text of Suluk Tenun. The data source used in this research is the text Suluk Tenun, a collection of Pura Pakualaman Library, located at pupuh VII Serat Piwulang Estri, and consists of 17 verses. The results showed that the text of Suluk Tenun was loaded with Javanese moral and cultural values. The symbols for the tools and the weaving process are used to describe the image of Javanese women in controlling their passions when they are married, such as telanjuk, kaki, kuping, kisi, and others. In the Suluk Tenun text, several images must have by a woman to be able to become a holy woman. The images are women who must be knowledgeable, able to control their passions, and able to rely on faith in God and the shari'a.